2017
DOI: 10.1021/acsmacrolett.7b00266
|View full text |Cite
|
Sign up to set email alerts
|

Dispersity under Scrutiny: Phase Behavior Differences between Disperse and Discrete Low Molecular Weight Block Co-Oligomers

Abstract: An experimental study is presented in which we compare the bulk phase behavior of discrete and (partially) disperse diblock co-oligomers (BCOs) with high χ–low N. To this end, oligomers of dimethylsiloxane (oDMS) and lactic acid (oLA) were synthesized, each having either a discrete number of repeat units or a variable block length. Ligation of the blocks resulted in oDMS–oLA BCOs with dispersities ranging from <1.00001 to 1.09, as revealed by mass spectroscopy and size exclusion chromatography. The phase behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 34 publications
(67 reference statements)
8
75
1
Order By: Relevance
“…It seems that uniformity of the blocks is more likely to create sharp interfaces, whereas disperse blocks can more readily create curved interfaces. These results are in accordance to the findings of Meijer and coworkers who showed that an increase of dispersity resulted in the widening of the space domain and a decrease of the overall degree of ordering.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It seems that uniformity of the blocks is more likely to create sharp interfaces, whereas disperse blocks can more readily create curved interfaces. These results are in accordance to the findings of Meijer and coworkers who showed that an increase of dispersity resulted in the widening of the space domain and a decrease of the overall degree of ordering.…”
Section: Resultssupporting
confidence: 93%
“…It was shown, that the phase separation of amphiphilic block co‐oligomers is sensitive to an increase of dispersity. Increasing the dispersity of blocks resulted in a widening of the domain spacing, increase of the stability of the microphase‐segregated state, and a decrease of the overall ordering . Additional investigations displayed the influence of the dispersity toward the self‐assembly of ABA‐type amphiphilic block co‐oligomers in aqueous solution .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our rationale was that PFOBiB would itself be a block (F13) with discrete dispersity, and possess a high χ interaction parameter with a polar homopolymer, which maintains a low N. PFOBiB was characterized by 1 H, 13 C and 19 F NMR spectroscopy ( Fig. S1-3 †), the excessive splitting observed in the 13 C spectrum is a result of carbon-fluorine coupling.…”
Section: Resultsmentioning
confidence: 99%
“…11 Dispersity (Đ) is a further important factor affecting bulk microphase separation, in which an increase in Đ has been shown to change morphology, increase domain spacing and decrease overall degree of order. [12][13][14] There have been several recent reports of sub-10 nm domain sizes. 4,[15][16][17][18] In order to push the lower size limit even further, SCFT suggests that the combination of a fluorinated block with a block comprising of highly polar repeat units could lead to domain spacings as small as 2 nm.…”
Section: Introductionmentioning
confidence: 99%